Konseling Lintas Budaya Gus Dur - Amalya El Fatihah Djovana; Bakhrudin All Habsy; Budi Purwoko; Mochamad Nursalim (Jurnal Bimbingan dan Konseling Islam, 2023)
Cross-cultural counseling has crucial relevance in this era of globalization. Where intercultural interactions are increasingly unavoidable, especially in Indonesia which is rich in cultural diversity. Having a counseling approach that considers these differences is crucial. Gus Dur, a renowned religious figure and spiritual leader, employs a counseling approach that blends Islamic religious values with local cultural insights. This study seeks to explore Gus Dur's cross-cultural counseling approach. It employs a qualitative research method, specifically a literature review. The analysis reveals that Gus Dur utilized a comprehensive counseling approach, emphasizing religious values, humanity, and local wisdom. These findings offer valuable insights for developing counseling methods rooted in local religious and cultural values, tailored to modern societal needs. Furthermore, they offer a fresh perspective on cross-cultural counseling practices, which could enhance counseling in Indonesia's diverse society.